HAK MEREK SEBAGAI JAMINAN GADAI UNTUK PERMODALAN UMKM INDUSTRI KREATIF KERAJINAN BATIK - Miftahur Rahman Hakim; Nur Kholidah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2019)
Creative industries are industries that intensify information and creativity by relying on stock of knowledge and ideas from Human Resources (HR). One type of creative industry is the batik creative industry. Industrial development was hindered by the inability to access capital, whether provided by the government or other financial institutions. The purpose of this study was to initiate the utilization of batik industry brand rights as collateral for pawning. This type of research uses library research (library research) obtained from literature sources through library research. Then use descriptive methods. Data collection techniques in this study are document studies. Then the data analysis includes: Descriptive Analysis (Analysis Descriptive) and Content Analysis (Content Analysis). The results of the study show that brand rights can be used as collateral for pawning. The use of brand rights as collateral is expected to support the growth of the UMKM batik creative industries in Pekalongan.Keywords:brand rights; collateral; mortgage.